Effects of inorganic nitrate on ischaemia-reperfusion injury after coronary artery bypass surgery: a randomised controlled trial. (October 2021) - Eriksson, Karin E.; Eidhagen, Fredrik; Liska, Jan; Franco-Cereceda, Anders; Lundberg, Jon O.; Weitzberg, Eddie
Abstract: Background: Nitric oxide (NO) is an important signalling molecule in the cardiovascular system with protective properties in ischaemia–reperfusion injury. Inorganic nitrate, an oxidation product of endogenous NO production and a constituent in our diet, can be recycled back to bioactive NO. We investigated if preoperative administration of inorganic nitrate could reduce troponin T release and other plasma markers of injury to the heart, liver, kidney, and brain in patients undergoing cardiac surgery. Methods: This single-centre, randomised, double-blind, placebo-controlled trial included 82 patients undergoing coronary artery bypass surgery with cardiopulmonary bypass. Oral sodium nitrate (700 mg×2) or placebo (NaCl) were administered before surgery. Biomarkers of ischaemia–reperfusion injury and plasma nitrate and nitrite were collected before and up to 72 h after surgery. Troponin T release was our predefined primary endpoint and biomarkers of renal, liver, and brain injury were secondary endpoints. Results: Plasma concentrations of nitrate and nitrite were elevated in nitrate-treated patients compared with placebo. The 72-h release of troponin T did not differ between groups. Other plasma biomarkers of organ injury were also similar between groups. Blood loss was not a predefined outcome parameter, but perioperative bleeding was 18% less in nitrate-treated patients compared with controls. Conclusion: Preoperative administration of inorganic nitrate did not influence troponin T release or other plasma biomarkers of organ injury in cardiac surgery. Clinical trial registration: NCT01348971 .